Oil spill modeling: Mapping the knowledge domain. (February 2020) - Nelson, Jake R; Grubesic, Tony H
The year 2019 marks the anniversary of two major US offshore oil spills: the 50th anniversary of the Santa Barbara spill and the 30th anniversary of the Exxon Valdez. The consequences of these spills are profound, echoing throughout countless environmental, ecological and social systems. Each spill sparked a flurry of research focusing on the analysis and documentation of spill impacts and responses. The purpose of this progress report is to evaluate oil spill modeling research as a knowledge domain. Using bibliometric analysis techniques, we constructed a co-citation network for exploring key areas of research and seminal papers to highlight the evolution of oil spill research over the past 50 years. The paper concludes with recommendations for future work, detailing the importance of connecting the physical and social sciences for deepening our understanding of oil spills and their broader implications for communities and the environment.